On extremal problems on classes of functions defined by integral moduli of continuity - Ligun, A. A.; Chernaya, E. V. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We obtain lower bounds for solutions of some extremal problems on classes of functions W rH 1 ω with integral modulus of continuity ω(t). Some of these bounds are regarded as exact.